(untitled) (Nexo Revista Científica, 2021)
The purpose of the present study is to develop a typology of university campuses reflecting all their diversity. The main attention is paid to the peculiarities of the location of the university campuses relative to the settlements, as well as their spatial planning arrangement. In general, depending on the spatial planning arrangement, three types of university campuses are defined and analyzed, namely, dispersed, dissected, and compact (local). The features of university complexes located in the metropolitan areas, largest, and large cities, as well as in medium and small cities, and outside of large settlements in the suburban area have been determined depending on the location of campuses relative to settlements. Besides, the authors have identified the ways of spatial planning development of existing university complexes and justified improving the spatial planning arrangement of university campuses. In general, four ways of the spatial development of existing universities are identified: purchasing facilities in the adjacent territory to expand the existing campus; placing the necessary additional facilities in the adjacent and other areas of the city, that is, integrating into the urban environment; creating an additional campus in a remote territory (often in the suburbs); and moving all or part of the university facilities to a new campus with a full-fledged infrastructure in another area of the city or suburb. The article provides examples of university campuses (complexes) in Russian cities for all the types considered, provided with the attached graphic schemes.